GOOD CORPORATE GOVERNANCE DISCLOSURES AND FINANCIAL PERFORMANCE: ISLAMIC SOCIAL REPORTING AND ZAKAH DISCLOSURES AS MEDIATING - Nanik Wahyuni; Novi Lailiyul Wafiroh (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2023)
This study examines the effect of good corporate governance (GCG) disclosure on financial performance proxied by Return on Assets. In addition, this study also aims to examine the mediating role of Islamic social reporting (ISR) disclosure and zakat disclosure on the financial performance of Islamic commercial banks (BUS). As a BUS, there is a responsibility to comply with zakat disclosure, not just ISR disclosure as stipulated rules. The quantitative research method with the selected research sample is all BUS registered on the IDX from 2018 to 2021. Data is processed using AMOS, where test results show that GCG disclosure directly affects ISR and zakat disclosure. ISR disclosure affects financial performance. Zakat disclosure does not affect financial performance. Indirectly, GCG disclosure affects financial performance through ISR disclosure. However, GCG disclosure does not affect financial performance through zakat disclosure. The implications of the results of this study show that GCG disclosure has a significant impact on company management to comply with reporting and disclosing ISR and zakat. This disclosure effort is a way for the company to convey information that the company has obediently carried out the provisions set as a BUS and can provide positive signals to the public to increase trust and impact company profitability.